Rural Development in Bangladesh since Independence: A Study on Progress and Performance - Hossain , Mohammad Ismail; Begum , Mst Esmat Ara Begum; Papadopoulou , Eleni; Semos, Anastasios (Asian Journal of Agriculture and Rural Development, 2012)
Rural development has been the core focus of the Bangladesh economic policies since her independence. The rural sector is pivotal to the country’s economic, social and political development. This paper examines the Bangladesh rural development policies, strategies and programs since Independence in 1971. Secondary data were used and collected from various sources especially from BBS and HIES. Data were analyzed using descriptive statistical tools such as mean and percentage to reach the objectives. Results of this study show that the share of agricultural sector in the country’s GDP has declined which is an indicator of a country’s progress from an agriculture-based to an export-oriented economy. The success of the agricultural and rural programs in Bangladesh is reflected in the reduction in the poverty incidence in the rural sector from almost 54 percent in the 1983-84 to about 35 percent in 2009-10. Development efforts of Bangladesh are governed by the twin objectives of achieving growth with equity and reducing poverty. The government policy has to some extent achieved the intended results but poverty and inequality are still significant and apparent. Hence, rural development continues to be an important agenda to the country’s development effort.